Pencatatan Sita Sertifikat Hak Atas Tanah di Kantor Pertanahan Kota Bandar Lampung - Pattikraton, Muhammad Aditya; Silviana, Ana (Universitas Batanghari Jambi, 2023)
This study aims to determine the recording of confiscation of certificates of land rights in the defense office of the city of Bandar Lampung. The method in this study uses a normative and empirical approach. The results of this study indicate that the legal implication of confiscation of land title certificates based on the Regulation of the Minister of Agrarian and Spatial Planning / Land Agency Number 13 Year 2017 Regarding the Procedure of Blocking and Confiscating is resulting the certificate holder temporarily unable to make the transfer of rights or the imposition of rights on his land until the revocation of the certificate of seizure of the land. Confiscation of certificates results in the suspension of land rights for the time being and will simultaneously freeze ownership of land. Furthermore, regarding the inhibiting factor for confiscation of land rights certificates, when recording is done manually, it is often the case that confiscation of seizure documents filed by the Ministry of Agriculture is not yet complete. the petitioner, as well as the lack of legal understanding related to legal standing confiscation of criminal, confiscated cases and confiscation due to forced letters. Suggestion of this research is that the Land Office should be more existent in disseminating information regarding the mechanism of confiscation recording at related institutions such as the Regional Police, Prosecutors, Courts and the public because the classification of criminal confiscation, confiscation of cases and confiscation due to forced letters.